Selected elements of socio-demographic status and lifestyle as factors determining subjective assessment of life in women after mastectomy - Skrzypczak, Magdalena; Czerniak, Urszula; Łaski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: The main objective of the study is to specify whether socio-demographic factors and physical activity result in differences in subjective assessment of life in women diagnosed with breast cancer. Material and methods : The study group consisted of 145 women who had been diagnosed with breast cancer. The women had undergone radical surgery, chemotherapy and radiotherapy. The participants filled in an anonymous questionnaire which contained a number of detailed questions relating to their socio-demographic standing, life style, condition and the current self-assessment of life after breast cancer. In order to assess the differences between groups made on the basis of socio-economic variables, the Kruskal-Wallis rank test was used. For a comprehensive assessment of relations, multiple correspondence analysis on the basis of Burt tables was used. Results : Their mean age at the time of the study was 57.1 years. The analysis of the effect of education and marital status on differences in the assessment of quality of life showed that these variables resulted in differences in the sphere related to social contacts (better educated women more often avoided social contacts) and in feeling of fatigue and exhaustion (the participants who were in a relationship indicated less fatigue and exhaustion). Conclusions : Mastectomy caused by breast cancer in women and related chemotherapy and radiotherapy negatively affect the physical and emotional condition of patients involving mental stress. Selected socio-demographic factors and elements of life style co-exist with each other, interpenetrating; thus the assessment of quality of life should comprise a set of factors and take into consideration their mutual interrelations.